2020
DOI: 10.7759/cureus.11587
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Challenge of Seronegative Autoimmune Encephalitis With Super-Refractory Status Epilepticus

Abstract: Autoimmune encephalitis is an immune-mediated syndrome, with sub-acute to chronic presentations, such as memory impairment, altered sensorium, behavioral abnormality, psychosis, and seizures. It poses a twofold diagnostic challenge: firstly, because of its variable clinical presentation and secondly, due to the wide variety of autoimmune antibodies causing it, which makes it difficult to identify the underlying etiology. Treatment should not be delayed due to pending laboratory workup, as early recognition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Current guidelines to definitively diagnose autoimmune encephalitis require confirmation of autoantibody presence or absence obtained from paraneoplastic, NMDA receptor, and other autoantibody panels that often cause significant delays in diagnosis and treatment [ 2 , 3 ]. Early recognition and initiation of treatment of seronegative encephalitis has been associated with improved patient outcomes, decreased mortality, and fewer cases of disease relapse [ 9 , 11 , 12 ]. It is our recommendation for clinicians suspicious of seronegative AE to utilize the criteria for ANPRA proposed by Graus et al which state that ANPRA diagnosis can be confirmed when the following four criteria are all met: (1) a patient experiences rapid progression of memory deficits, AMS, or psychiatric symptoms within three months, (2) exclusion of well-defined syndromes of autoimmune encephalitis, (3) absence of defined autoantibodies in serum or CSF, and (4) reasonable exclusion of alternative causes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidelines to definitively diagnose autoimmune encephalitis require confirmation of autoantibody presence or absence obtained from paraneoplastic, NMDA receptor, and other autoantibody panels that often cause significant delays in diagnosis and treatment [ 2 , 3 ]. Early recognition and initiation of treatment of seronegative encephalitis has been associated with improved patient outcomes, decreased mortality, and fewer cases of disease relapse [ 9 , 11 , 12 ]. It is our recommendation for clinicians suspicious of seronegative AE to utilize the criteria for ANPRA proposed by Graus et al which state that ANPRA diagnosis can be confirmed when the following four criteria are all met: (1) a patient experiences rapid progression of memory deficits, AMS, or psychiatric symptoms within three months, (2) exclusion of well-defined syndromes of autoimmune encephalitis, (3) absence of defined autoantibodies in serum or CSF, and (4) reasonable exclusion of alternative causes [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seronegative autoimmune encephalitis is a rare subtype of autoimmune encephalitis that occurs when there is no identifiable, pathologic autoantibody in either the cerebrospinal fluid (CSF) or serum of the patient. At present, the lack of identifiable autoantibodies in seronegative AE is hypothesized to be caused by unidentified autoantibodies that have not currently been discovered [ 8 , 9 ]. Ultimately, the lack of diagnostic testing to confirm seronegative AE results in diagnostic challenges and delayed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An important though problematic area in this field is the entity of seronegative AE, which may account for up to 50% of all AE (74). A 2016 consensus paper proposed a set of diagnostic guidelines that do not rely on antibody status, providing a basis for identification of seronegative cases (75).…”
Section: Seronegative Aementioning
confidence: 99%